2014
DOI: 10.1111/jsm.12361
|View full text |Cite|
|
Sign up to set email alerts
|

A Guide for Inflatable Penile Prosthesis Reservoir Placement: Pertinent Anatomical Measurements of the Retropubic Space

Abstract: Introduction The primary concern for many prosthetic urologic surgeons in placing the three-piece inflatable penile prosthesis (IPP) is the concept of “blind reservoir placement.” Extensive reports permeate the literature regarding bladder, bowel, vascular, and various hernial complications occurring while attempting to place the reservoir into the retropubic space. However, despite these widely documented complications, there is a paucity of published literature on surgically pertinent anato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…While rare, there have been several reports of complications related to this approach including bladder perforation, avulsion of a branch of the external iliac vein, postoperative venous compression syndrome, herniation of the reservoir, and direct inguinal herniation of intra-abdominal contents ( 11 ). Cadaveric studies have shown the bladder and external iliac vessels can be as close as two centimeters from the inguinal ring, which is closer than previously appreciated ( 12 ). Certain patient factors such as prior robotic-assisted laparoscopic prostatectomy or radical cystectomy can further complicate the anatomy by violating the space of Retzius.…”
Section: Reservoir Placement and Intra-abdominal Injuriessupporting
confidence: 59%
“…While rare, there have been several reports of complications related to this approach including bladder perforation, avulsion of a branch of the external iliac vein, postoperative venous compression syndrome, herniation of the reservoir, and direct inguinal herniation of intra-abdominal contents ( 11 ). Cadaveric studies have shown the bladder and external iliac vessels can be as close as two centimeters from the inguinal ring, which is closer than previously appreciated ( 12 ). Certain patient factors such as prior robotic-assisted laparoscopic prostatectomy or radical cystectomy can further complicate the anatomy by violating the space of Retzius.…”
Section: Reservoir Placement and Intra-abdominal Injuriessupporting
confidence: 59%
“…Previous surgery in the area, pelvic radiation therapy, and an anastomotic leak with perivesical urinoma following radical prostatectomy are situations where excessive scar may be encountered. The iliac artery and vein are about 1 inch lateral to the pocket where the reservoir is placed [16]. Injury to either of these vessels is catastrophic [17].…”
Section: Reservoir Placement and Iliac Vessel Injurymentioning
confidence: 99%
“…In fact, if the IPP was left inflated at the end of surgery (to minimize corporal bleeding with compression), the doctor still had to deflate the prosthesis, resulting in additional patient discomfort. Interestingly, a patient satisfaction study found that for many patients, the most negative experience of the surgery was the dressing removal/deflation of the IPP [40].…”
Section: Postoperative Carementioning
confidence: 99%